Implementasi Metode Analytical Hierarchy Process (AHP) untuk Evaluasi Pemasok Daging Sapi (Studi Kasus: Restoran Nominomi Delight, Jakarta) - Hanifah, Fadhilah; Wiranthi, Elpawati Puspi Eko (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2021)
The purpose of this research is to develop a performance appraisal method to get the priority order of four restaurant beef suppliers based on the weight of the selection criteria and by showing the indicators of each criterion, using the Vendor Performance Index and the Analytical Hierarchy Process (AHP) method. There are seven main criteria for assessing supplier performance, namely quality, cost, delivery, flexibility, responsiveness, solutions, and relationships which are then translated into thirty-eight sub criteria or indicators. With the AHP method, weights obtained from the seven criteria in the order of quality (0.371), cost (0.256), delivery (0.101), solution (0.078), flexibility (0.070), responsiveness (0.069), and relationship (0.055). The results of supplier selection based on the AHP method obtained the weight in the order of priority of suppliers, namely PT Sukanda Djaya (0.377). PT Indoguna Utama (0.349). Santosa Agrindo (0.146), and Amino Meat (0.128).